STRATEGI KEPEMIMPINAN KEPALA DESA DALAM MENINGKATKAN DISIPLIN KERJA PERANGKAT DESA BIJAEPUNU KECAMATAN MOLLO UTARA - Enika Kabnani; Melly Putriyani Dethan; Nusriwan Chrismanto Soinbala (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Village head leadership plays a crucial role in improving the work discipline of village officials to support effective public services. However, preliminary observations in Bijaepunu Village indicate that several village officials still demonstrate low discipline, particularly in attendance, compliance with work regulations, and responsibility in completing tasks. This study aims to describe the leadership strategies of the village head in improving the work discipline of village officials in Bijaepunu Village, Mollo Utara District. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The informants consisted of the village head and village officials. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings reveal that the village head’s leadership strategies include setting vision and mission, direct supervision of attendance and task performance, gradual decision-making through warnings and sanctions, and providing motivation through meetings and personal approaches. These strategies positively impacted the work discipline of some village officials, although consistency remains an issue for others. Therefore, village head leadership strategies play an important role in fostering work discipline and enhancing public service quality.